Identification of a High-risk Subgroup With Malignant Mitral Valve Prolapse Who Are Predisposed to Sudden Cardiac Death: A Review. Issue 1 (31st August 2020) - Russo, Ronald; Maan, Abhishek; Apostolidou, Eirini; Khorasani-Zadeh, Arshia; Byrnes, Sean; Chebaya, Philip; Beale, Robert; Abbasi, Mohammad Usama; Beale, Charles
Abstract : Mitral valve prolapse (MVP) affects approximately 170 million people worldwide; however, phenotypically, there is a wide variety of heterogeneity. In particular subsets, the incidence of sudden cardiac death is calculated to be 998 per 100, 000 person-years, which is significantly increased when compared with the general population of MVP patients. Individuals with high-risk features have been identified as young females with bileaflet MVP and electrocardiogram findings of frequent complex ectopy, ST-T wave changes, and inferior T wave inversions. Supplemental imaging modalities in this subgroup demonstrate redundant leaflets and chordae on 2-dimensional transthoracic echocardiography along with varying severity of mitral annular disjunction. Detailed morphologic assessment by 3-dimensional echocardiography provides a quantitative assessment of annular disjunction along with left ventricular longitudinal and basal circumferential strain patterns. Late gadolinium enhancement on cardiac magnetic resonance imaging identifies diffuse and isolated left ventricle fibrosis involving the fascicles and papillary muscles, which has been visualized in isolation during autopsy. Findings of this review propose that sudden cardiac death as a result of malignant arrhythmias arises from automaticity, complex ectopy, and reentry at the level of the fascicles and papillary muscles. The repetitive mechanical stress provides a nidus for the development of both micro- and macrofibrosis easily identified by late gadolinium enhancement on cardiac magnetic resonance imaging. Escalation to electrophysiology studies and early intervention could provide new targeted lifesaving therapies.